2015
DOI: 10.1038/mt.2015.48
|View full text |Cite
|
Sign up to set email alerts
|

[ 18 F]FHBG PET/CT Imaging of CD34-TK75 Transduced Donor T Cells in Relapsed Allogeneic Stem Cell Transplant Patients: Safety and Feasibility

Abstract: Described herein is a first-in-man attempt to both genetically modify T cells with an imagable suicide gene and track these transduced donor T cells in allogeneic stem cell transplantation recipients using noninvasive positron emission tomography/computerized tomography (PET/CT) imaging. A suicide gene encoding a human CD34-Herpes Simplex Virus-1-thymidine kinase (CD34-TK75) fusion enabled enrichment of retrovirally transduced T cells (TdT), control of graft-versus-host disease and imaging of TdT migration and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…Different radioactive compounds are routinely injected in patients for clinical diagnosis. [ 18 F]FHBG appears to be an effective tool for obtaining biological information in a non-invasive manner and has been already tested in a clinical trial, in patient with leukaemia after infusion of Tcell genetically modified [ 7 , 8 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different radioactive compounds are routinely injected in patients for clinical diagnosis. [ 18 F]FHBG appears to be an effective tool for obtaining biological information in a non-invasive manner and has been already tested in a clinical trial, in patient with leukaemia after infusion of Tcell genetically modified [ 7 , 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…[ 18 F]FHBG is a PET imaging radiotracer that is easily transferrable to human applications [ 7 , 8 ]. PET scans allow radiolabelled markers and their interactions with biochemical processes to be imaged in living subjects.…”
Section: Introductionmentioning
confidence: 99%
“… 92 Eissenberg et al recently described an early clinical work in which T-cells were modified with a suicide gene (CD34-HSV1tk) whose distribution could be tracked over time using 9-[4-(18 F)fluoro-3-hydroxymethyl-butyl] guanine ([ 18 F]FHBG). 93 A similar approach had been reported by Dubey et al using 9-[4-[18F]fluoro-3-(hydroxymethyl) butyl]guanine ([ 18 F]FHBG) to image splenic T-cells bearing the HSV1-sr39tk PET reporter gene. 94 Earlier precursor work in 2001 by Ponomarev et al used [ 124 I]-(2′-deoxy-2′-fluoro-β- d -arabinofuranosyl)-5-iodouracil to detect T-cell activation in vivo using an HSV1tk/green fluorescent protein reporter system in rats.…”
Section: Imaging During Immunotherapy Using Tumor-specific T-cellsmentioning
confidence: 93%
“…Yaghoubi et al also studied human pharmacokinetics and dosimetry of [ 18 F] FHBG with ten healthy volunteers and showed no toxicity (14). The safety and feasibility of radiolabeled [ 18 F] FHBG PET is studied in several clinical fields including recurrent glioma (7,15). Keu et al reported the in vivo kinetics of CAR-T cells detected by PET scan using [ 18 F] FHBG (16).…”
Section: Ctl Tracking Using [ 1 8f] Fhbgmentioning
confidence: 99%